2011
DOI: 10.1177/1758834011412656
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab for the treatment of bone metastases in breast cancer: evidence and opinion

Abstract: Abstract:Introduction: Denosumab, a fully human monoclonal antibody, targets the receptor activator of nuclear factor-kappaB (RANK) ligand, a protein essential for osteoclast differentiation, activity and survival. Loss of osteoclasts from the bone surface reduces bone turnover and bone loss in malignant and benign diseases. In breast cancer, bone metastases are frequently observed; cancer treatment-induced bone loss (CTIBL) may result as a consequence of endocrine treatment or chemotherapy. Furthermore, precl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 65 publications
0
18
0
2
Order By: Relevance
“…[23] However, zoledronic acid’s potential as a standard of care against bone destruction is not yet fully supported, because it still offers only moderate benefits in the patients. [24] Development of more effective therapies is important for those patients with osteolytic bone destruction.…”
Section: Discussionmentioning
confidence: 99%
“…[23] However, zoledronic acid’s potential as a standard of care against bone destruction is not yet fully supported, because it still offers only moderate benefits in the patients. [24] Development of more effective therapies is important for those patients with osteolytic bone destruction.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of mandibular bone invasion, it is possible to treat the cancer with OPG locally because oral SCC cells invade from cortical bone, and the tumor and defect area are at the surface of the body. However, recent reports showed that the observed incidence of osteonecrosis of the jaw was comparable to that with bisphosphonates (52,53). Therefore, it is important to carefully consider the dosage and schedule of administration to avoid any side-effects of local injection of OPG or denosumab before the realization of the clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, jaw osteonecrosis developed in 2.0% of the patients in the denosumab group and 1.4% in the zoledronic acid group, with no significant difference between the groups (P ¼ 0.39). Denosumab showed better outcomes with respect to the delayed onset of SREs and the inhibitory effect on the onset of SREs than zoledronic acid, suggesting that denosumab was well tolerated by the majority of patients (Table 1) (19).…”
Section: Efficacymentioning
confidence: 99%